2010
DOI: 10.1037/a0020495
|View full text |Cite
|
Sign up to set email alerts
|

Implicit affective cues and attentional tuning: An integrative review.

Abstract: A large and growing number of studies support the notion that arousing positive emotional states expand, and that arousing negative states constrict, the scope of attention on both the perceptual and conceptual levels. However, these studies have predominantly involved the manipulation or measurement of conscious emotional experiences (e.g., subjective feelings of happiness or anxiety). This raises the question: Do cues that are merely associated with benign versus threatening situations, but that do not elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
288
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(327 citation statements)
references
References 191 publications
22
288
3
4
Order By: Relevance
“…Fluid movement enhanced creative but not analytic performance (only the former requires fluid thought), and the influence of fluid movement on creativity was not a result of enhanced conscious experiences of positive affect. One possibility that remains and awaits future research is that fluid movement serves as an implicit affective cue, suggesting a safe environment where explorative creative processing is encouraged (see Friedman & Förster, 2010;Topolinski & Reber, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fluid movement enhanced creative but not analytic performance (only the former requires fluid thought), and the influence of fluid movement on creativity was not a result of enhanced conscious experiences of positive affect. One possibility that remains and awaits future research is that fluid movement serves as an implicit affective cue, suggesting a safe environment where explorative creative processing is encouraged (see Friedman & Förster, 2010;Topolinski & Reber, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, real-world variables, such as the colour of packaging could be manipulated to trigger global processing (see Friedman & Forster, 2010;and Forster & Dannenberg, 2010, p182) in order to increase consumer's enjoyment of "tactile" products such as skin creams. According to the GLOMOsys model (Forster & Dannenberg, 2010), global-local carry-over effects should occur across sensory modalities, therefore future studies could investigate whether priming global/local processing in the auditory, or olfactory senses (e.g., by asking participants to rate the pleasantness of a piece of music/smell, or distinguish the component parts), also affects the subsequent pleasantness of touch.…”
Section: Discussionmentioning
confidence: 99%
“…This attention bias was assessed with a visual matching task (see Kimchi & Palmer, 1982) presumed to reflect automatic perceptual and attentional processing (Andres & Fernandes, 2006;Poirel, Pineau, & Mellet, 2006). Previous research showed that individuals with a constricted attentional focus due to avoidance motivation exhibit a local relative to global processing bias (Friedman & Förster, 2010;Gasper, 2004). Performing the first step of the experimental chain approach revealed the predicted effect: Red negatively influenced intellectual performance compared to a gray baseline condition (Maier et al, 2008).…”
Section: Mediation Of the Influence Of Red On Intellectual Performancementioning
confidence: 99%
“…Accordingly, viewing red in an achievement context is posited to impair performance attainment because it evokes avoidance, which in turn, is inimical to performance. The activation, operation, and influence of avoidance motivation in this hypothesized red effect is thought to take place outside of conscious awareness; that is, it acts in an implicit rather than explicit fashion (see Friedman & Förster, 2010).…”
Section: What Is Context?mentioning
confidence: 99%
See 1 more Smart Citation